2017
DOI: 10.17161/jas.v0i0.5870
|View full text |Cite
|
Sign up to set email alerts
|

Parent Coaches’ Experiences and Insights into a Youth Soccer Program

Abstract: Municipal governments continue to struggle with decreased funding. In order to offset depleting funds, agencies rely on volunteers to provide resources to the public. In youth sport programs, parents provide much of the support, and it is estimated that 90% of youth sport coaches are parents. Given that parents have been instrumental in youth sport programs, the purpose of this study was to understand parents' experiences and insights associated with volunteering by using a youth soccer program located in a mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Previous studies have revealed both positive (e.g., children receiving special attention, praise, and being involved in decision-making) and negative features (e.g., control, harsher criticism) of parent-coaching (Elliott & Drummond, 2017;Kerins et al, 2017;Schmid et al, 2015;Weiss & Fretwell, 2005). These previous studies have provided few insights into how and why there are (seemingly contradictory) positive and negative outcomes of parent-coaching.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…Previous studies have revealed both positive (e.g., children receiving special attention, praise, and being involved in decision-making) and negative features (e.g., control, harsher criticism) of parent-coaching (Elliott & Drummond, 2017;Kerins et al, 2017;Schmid et al, 2015;Weiss & Fretwell, 2005). These previous studies have provided few insights into how and why there are (seemingly contradictory) positive and negative outcomes of parent-coaching.…”
Section: Discussionmentioning
confidence: 98%
“…Following Research Ethics Board approval, participants were recruited through criterion sampling (Patton, 2002). Fathers and daughters were targeted to address limitations of previous studies that have focused on fathers or parents coaching boys (e.g., Elliott & Drummond, 2017;Kerins et al, 2017;Weiss & Fretwell, 2005). To be eligible, parents must have been fathers who coached their own daughter for a minimum of one season.…”
Section: Participants and Recruitmentmentioning
confidence: 99%
See 3 more Smart Citations